Two new species of Xyalidae Chitwood, 1951 (Nematoda, Monhysterida) from Chinese Sea Area - Li, Ting; Ban, Shuyan; Huang, Yong (Zootaxa, 2023)
Two new nematode species of the family Xyalidae were found in the intertidal zone of the Chinese coast, and they are described here as Daptonema sinica sp. nov. and Metadesmolaimus bulbosus sp. nov. Daptonema sinica sp. nov. is characterised by a relatively large body with a broad funnel-shaped buccal cavity; relatively long cephalic setae; a circular amphidial fovea posterior to the buccal cavity; slender spicules bending into a hook shape in the posterior half; a small plate-like gubernaculum without apophysis; and a conico-cylindrical slender tail with terminal setae. Metadesmolaimus bulbosus sp. nov. can be identified by its large buccal cavity, long cervical setae, multiple bulb-like pharyngeal muscular swellings, conico-cylindrical tail narrowing abruptly immediately posterior to the cloaca, straight clavated spicules with a broad proximal end and hooked distal end, and gubernaculum absent. An updated dichotomous key to the species of Metadesmolaimus is given.